2005
DOI: 10.1109/tps.2005.845302
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of pulsed corona discharge under supercritical conditions

Abstract: Supercritical carbon dioxide is a medium with unique properties and variety of applications in modern green chemistry.The generation of pulsed corona discharge in supercritical CO 2 is studied experimentally for point-to-plane and wire-to-plane geometries. The low breakdown voltages recorded near the critical point are attributed to peculiarities of electron kinetics in a medium characterized by high spatial inhomogeneity and enhanced cluster formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Indeed, operation at atmospheric pressure is a natural choice for discharges with characteristic lengths of hundreds of microns. Nonetheless, operation at pressures as low as a few tens of mTorr47 and as high as several tens of atmospheres48, 49 have also been reported. Operation at lower pressure is preferred for applications such as gas monitoring in the feed/exhaust pipes of a large‐scale vacuum system 50.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, operation at atmospheric pressure is a natural choice for discharges with characteristic lengths of hundreds of microns. Nonetheless, operation at pressures as low as a few tens of mTorr47 and as high as several tens of atmospheres48, 49 have also been reported. Operation at lower pressure is preferred for applications such as gas monitoring in the feed/exhaust pipes of a large‐scale vacuum system 50.…”
Section: Introductionmentioning
confidence: 99%
“…The insulation strength of SCCO 2 was about 10 times higher than that of SF 6 at 0.5kPa which is the usual gas pressure of high power switchgear. This means that the insulation strength of SCCO 2 is enough to substitute SF 6 gas which has been used in electrical apparatus. Using the result, we expect that the time for switching and dielectric recovery could be reduced using SCCO 2 fluid as an insulating medium.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, supercritical carbon dioxide (SCCO 2 ) has been widely used because it is nontoxic, nonflammable, low cost and low critical temperature of 304K. Using electrical discharge plasma inside supercritical SCCO 2 has been emerged as a useful chemical reaction tool which could be applied environment and biomedical fields [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Argon is also inexpensive and its optical transparency is superior to that of carbon dioxide since it is monatomic. Lock et al initiated pulsed corona discharge under supercritical conditions, and reported that the breakdown voltage for a wire-in-cylinder configuration is three times lower than estimates based on Paschen's law due to the large in-homogeneties in the density of the supercritical fluid near the critical point [3]. Recently, the discharge plasma in supercritical fluids is an underdeveloped field, and the pre-breakdown phenomena are not well understood.…”
Section: Introductionmentioning
confidence: 99%